¿Sospechar para igualar? Un análisis «estricto» de la doctrina de las categorías sospechosas a partir de la jurisprudencia del Tribunal Constitucional peruano y la Corte Interamericana de Derechos Humanos - Valdivia Aguilar, Trilce (2020)
This paper is an introductory study of the doctrine of suspect classifications based on the case law of the Peruvian Constitutional Court and the Inter-American Court of Human Rights. It aims to describe the special features of this doctrine as well as to critically analyze its proposed justification and the consequences of its application: The strict scrutiny test. To achieve this purpose, this work describes the case law in which both courts have explicitly mentioned this doctrine. Based on this study, the author identifies that the foundation of this doctrine lies in the notion of equality as recognition of vulnerable groups and that both tribunals have established as its main effect the application of a strict scrutiny test. Finally, the author critically assesses these jurisprudential findings.